Pathophysiological Response to Hypoxia - From the Molecular Mechanisms of Malady to Drug Discovery: Drug Discovery for Targeting the Tumor Microenvironment - Hideko Nagasawa (Elsevier, 2011)
The tumor microenvironment, characterized by regions of hypoxia, low nutrition, and acidosis due to incomplete blood vessel networks, has been recognized as a major factor that influences not only the response to conventional anti-cancer therapies but also malignant progression and metastasis. However, exploiting such a cumbersome tumor microenvironment for cancer treatment could provide tumor-specific therapeutic approaches. In particular, hypoxia is now considered a fundamentally important characteristic of the tumor microenvironment in which hypoxia inducible factor (HIF)-1-mediated gene regulation is considered essential for angiogenesis and tumor development. Additional oxygen sensitive signaling pathways including mammalian target of rapamycin (mTOR) signaling and signaling through activation of the unfolded protein response (UPR) also contribute to the adaptation in the tumor microenvironment. This in turn has led to the current extensive interest in the signal molecules related to adaptive responses in the tumor microenvironment as potential molecular targets for cancer therapy against refractory cancer and recurrence in preparation for the aging society. Therefore, we should focus on the drug discovery for targeting the tumor microenvironment to develop tumor-specific cytostatic agents including angiogenesis inhibitors. In this paper, the development of hypoxia-selective prodrugs, HIF-1 inhibitors, and modulators of the tumor microenvironment will be discussed. Keywords:: hypoxia, tumor microenvironment, hypoxia inducible factor (HIF)-1, bioreductive activation